Agostinho e Aristóteles no conhecimento intelectual humano segundo Tomás de Aquino - Soler, Adriano Martins (2014)
The theory of knowledge in Aquinas is an interest target of many researchers of the period. Its importance is singular, among other things, due to the disruption that it causes between the established doctrine about knowledge itself, the Augustinian doctrine of divine illumination and some orders, that until that moment, remained faithful to (Augustinian s). This dissertation aims, from the articles five and six from question 84 inserted in the first part of the Summa of theology of Thomas Aquinas, return to this issue that is far from being exhaustedly explored given its richness and complexity. Therefore, we present, at first, the historical context in which the Summa of Theology was written, as well as what it is in its shape and utility. Subsequently, we turn our attention to its first part. In it, Thomas refers to God and to what proceeds from him, better said, the work of the creation and its action in the world, to then, be able to focus on the group of questions regarding human knowledge, ie, questions 84 - 89 Next, we turn our attention to the question 84 and its articles, exposing its structure and systematize, to finally be able to concentrate on the axioms of articles five and six. In them, we realized Thomas skillfully taking advantage of auctoritates technique to harmonize Augustinian and Aristotle thinking regarding the theory studied in this paper